Understanding service connectivity based on digital serendipity: An actor-network approach. (August 2022) - Chang, Mi; Park, Ju Hong
Abstract: The term smart city is an emerging urban concept that provides optimal public services in a city as a hybrid combination of people, technology, and place. However, previous research does not consider various factors and either depends on technology development or studies of human and non-human factors separately. In addition, even if the relationship between human and non-human elements is analyzed, it is difficult to realize the analyzed content as a service for real users. The actor-network theory (ANT), established by Latour, is a theory that provides a deep understanding of the underlying mechanisms of smart cities by illustrating how the networks of human and non-human actors create the weave of unpredictable connections. We call this digital serendipity when it is realized as a service from this network. This study aims to analyze the actor-network, where digital serendipity can occur, and apply it to increase the possibility of service formation. To this end, we collect the location data of users on a campus as a living lab and analyze the network between users and buildings. Further, by applying the results of the analyzed network, we develop a web-based application as an example where digital serendipity can be implemented for voluntary service formation. To verify the service connectivity, we conducted a test utilizing library book rental data.